2018
DOI: 10.1116/1.5023918
|View full text |Cite
|
Sign up to set email alerts
|

Reactive sputter deposition of piezoelectric Sc0.12Al0.88N for contour mode resonators

Abstract: Substitution of Al by Sc has been predicted and demonstrated to improve the piezoelectric response in AlN for commercial market applications in radio frequency filter technologies. Although cosputtering with multiple targets have achieved Sc incorporation in excess of 40%, industrial processes requiring stable single target sputtering are currently limited. A major concern with sputter deposition of ScAl is the control over the presence of non-c-axis oriented crystal growth, referred to as inclusions here, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…These values are an order of magnitude lower than that for the AlN film with a similar thickness and microstructure (∼51 W m −1 K −1 ) and 2 orders of magnitude lower than a single-crystal epitaxial film of AlN (∼320 W m −1 K −1 ). 28 It should be noted that the average columnar (lateral) grain size resulting from the reactive sputter deposition process 18,29 was consistent (∼35 nm; Figure 1c) among all the AlN and Al 1−x Sc x N films investigated in this work. Consequently, from a practical perspective, the reduction in thermal conductivity underscores the intrinsic trade-off between piezoelectric and thermal performance in the Al 1−x Sc x N solid solution.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…These values are an order of magnitude lower than that for the AlN film with a similar thickness and microstructure (∼51 W m −1 K −1 ) and 2 orders of magnitude lower than a single-crystal epitaxial film of AlN (∼320 W m −1 K −1 ). 28 It should be noted that the average columnar (lateral) grain size resulting from the reactive sputter deposition process 18,29 was consistent (∼35 nm; Figure 1c) among all the AlN and Al 1−x Sc x N films investigated in this work. Consequently, from a practical perspective, the reduction in thermal conductivity underscores the intrinsic trade-off between piezoelectric and thermal performance in the Al 1−x Sc x N solid solution.…”
Section: Resultssupporting
confidence: 62%
“…These stress values were determined via wafer curvature measurements . As reported elsewhere, the density of AOGs tended to be lower in films with higher substrate bias …”
Section: Results and Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Although it has been reported that the k eff 2 can be increased by about four times compared to un-doped AlN for a doping concentration of 40%, the improvement comes at the cost of significant reduction in Q [ 129 ]. Possible reasons for degradation in Q are related to the formation of inclusions and film stress during the film deposition process [ 130 ]. Besides optimizing the process parameters to avoid inclusions, as well as controlling film stress, an interesting Q-enhancement strategy in terms of materials advances has been to combines the ScAlN film with single crystal silicon to realize high-Q ScAlN-on-Si TPoS LVRs [ 131 ].…”
Section: Discussionmentioning
confidence: 99%
“…1(c)-(e)], since it was first introduced, has found its way into commercial products at moderate doping concentrations [30]. Extensive research has gone into reactive sputtering of Sc-doped AlN targets that can produce uniform doping concentration and stress across wafers [33]. Tradeoffs between doping levels and experimentally attainable Q have been renewed every year, producing higher and higher k 2 with nearly no sacrifice of Q [28].…”
Section: Higher Coupling Operational Modesmentioning
confidence: 99%